Equivalence Challenges in Machine Translation: An Analysis of Google Translate Output through Mona Baker's Theory (2011) and Post-Editing Strategies - Marhamah; Hidayati, Dini; Prasatyo, Bayu Andika (CV ODIS, 2024)
This research aims to analyse the level of equality based on Mona Baker's theory translated by J.K. Rowling's